PENGARUH RASIO LIKUIDITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Taslim, Fadli Ali (Jurnal Manajemen Sinergi, 2015)
This research aims to understand the effect of liquidity, activity, and profitability toward the companyâ€™s value throught dividend policy as intervening variable. This researchâ€™s population is manufacturing companies listed in Indonesia Stock Exchange (BEI). Samples are chosen by the method of purposive sampling which resulted in 21 samples with 5 years time span that is from 2010 to 2014. Research results shows that liquidity (CR) has positive effect towards companyâ€™s value which is proxied with Tobins Q, but also has a significant and negative effect towards companyâ€™s value through dividend policy (DPR).Â Activity (TATO) has negative effect towards companyâ€™s value which isÂ proxied with Tobins-Q, but it has positive effect towards companyâ€™s value through dividend policy (DPR). Profitability (ROE) has negative effect towards companyâ€™s value which is proxied with Tobins-Q, but has positive effect towards companyâ€™s value through dividend policy (DPR).